2021
DOI: 10.1155/2021/8021362
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Osseous Choristoma in an 11-Year-Old Female: A Case Report and Literature Review Focusing on Pediatric Cases

Abstract: Osseous choristoma is an uncommon benign lesion characterized by the presence of ectopic mature bone within soft tissue. In most cases, these lesions occur on the dorsum of the tongue in patients in their third and fourth decades of life. This article describes a case of lingual osseous choristoma in a pediatric patient. An eleven-year-old girl with a lingual mass was referred to our hospital from a dental clinic. Total excisional biopsy and histological examination were performed, and osseous choristoma was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…With less than 100 reported cases, lingual osseous choristoma is considered a rare pathology. Analyzing the age of patients, it ranges from 5 to 89 years, mostly affecting young patients in the second and third decade of life [4,5,6] . This lesion has female predilection with a ratio of almost 2.7:1, and in 2/3 of cases it is located in the posterior tongue region of the dorsum anterior to papillae circumvallate and foramen cecum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With less than 100 reported cases, lingual osseous choristoma is considered a rare pathology. Analyzing the age of patients, it ranges from 5 to 89 years, mostly affecting young patients in the second and third decade of life [4,5,6] . This lesion has female predilection with a ratio of almost 2.7:1, and in 2/3 of cases it is located in the posterior tongue region of the dorsum anterior to papillae circumvallate and foramen cecum.…”
Section: Discussionmentioning
confidence: 99%
“…This lesion has female predilection with a ratio of almost 2.7:1, and in 2/3 of cases it is located in the posterior tongue region of the dorsum anterior to papillae circumvallate and foramen cecum. Literature reports cases with osseous choristomas located in the lateral edge, medium third of the tongue, anterior third and base of the tongue, according to frequency in that order [3,4] . Dimensions can vary from 3 mm to 50 mm in the largest diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, regarding pediatric cases, Arimoto et al reviewed the literature and found 17 cases, including 13 of them being females. No identifiable reason for the sexual predisposition and no major differences in clinicopathological characteristics between pediatrics and adults were observed [ 7 ]. The most frequently affected region is the posterior third of the tongue dorsum near the foramen caecum and circumvallate papillae accounting for 90% of cases, and 10% are on the middle third of the tongue [ 8 ].…”
Section: Discussionmentioning
confidence: 99%